Михаил Иванович Ситенко - Костриков В.С.; Скоблин А.П.; Kostrikov V.S.; Skoblin A.P. (Харьковское областное издательство, 1958)
Автори книги знайомлять читачів з біографією, науково-педагогічною, лікувальною, хірургічною та громадською діяльністю видатного українського вченого-патріота, основоположника ортопедії та травматології в Україні та засновника однієї з найкрупніших і найавторитетніших шкіл травматологів та ортопедів у Радянському Союзі. Книга розрахована на масового читача.

The authors of the book introduce readers to the biography, scientific and pedagogical, medical, surgical and public activities of the outstanding Ukrainian scientist-patriot, the founder of orthopedics and traumatology in Ukraine and the founder of one of the largest and most authoritative schools of traumatologists and orthopedists in the Soviet Union. The book is designed for a mass readership.
Mikhail Ivanovich Sytenko